Implementation of the One Village One Product (OVOP) Program on Virgin Coconut Oil (VCO) Small and Medium Enterprises in Nagrak Village, Buahdua District, Sumedang Regency - Putri, Nabila; Mulyani, Sri; Ramadhina, Retno (Abdi Masyarakat, 2024)
The OVOP program aims to develop the potential of local natural resources into regional superior products. One of the natural resources identified as having potential in Nagrak Village is coconut which is processed into Virgin Coconut Oil (VCO). Virgin coconut oil (VCO) is a processed product from coconut that is clear, tasteless, and has a distinctive coconut odor. to find out the researchers used descriptive qualitative research methods. in this study researchers collected data using observation, interviews and documentation techniques. The implementation of the OVOP program involves community participation, collaboration with business development assistance institutions such as BUMDes and Bank BJB, as well as evaluation and monitoring. The obstacles faced by VCO SMIs include marketing problems because many people in Nagrak Village do not know and product packaging. The solution provided for this problem is socialization in the form of product launching attended by the village community, as well as packaging branding. with this program, it is hoped that VCO SMEs can be more widely known and provide economic value, especially in Nagrak Village.